Analisis Pengetahuan Dan Sikap Terhadap Kepatuhan Pasien Pada Pengunan Amoksisilin Di Pukesmas Cibadak Sukabumi - Adinda Nurul Fadlilah Khairunnisa; Mally Ghinan Sholih (Jurnal Ilmiah Wahana Pendidikan, 2022)
Infectious diseases are still one of the public health problems in Indonesia that often occur, especially in developing countries. The high prevalence of infectious diseases causes the high use of antibiotics, one of which is amoxicillin. Inappropriate use of amoxicillin can lead to antibiotic resistance. This study aims to determine the relationship between knowledge and attitudes towards medication adherence at the Cibadak Public Health Center, Sukabumi. This research method is an analytic survey with a cross sectional research design. The study was conducted at the Cibadak Sukabumi Public Health Center and the time of its implementation was in February - April 2022. The sampling technique used accidental sampling with a total sample of 286 respondents. The questionnaire used in this study was knowledge, attitude and Morisky Medication Adherence scale (MMAS-8). The data were statistically analyzed using univariate and bivariate methods using the Chi-square test from the SPSS 25 program. The results obtained were high patient knowledge of amoxicillin at Cibadak Sukabumi Public Health Center (83.2%). The attitude of the patients at the Cibadak Sukabumi Public Health Center (89.2%) was classified as good. Adherence to taking amoxicillin in patients at the Cibadak Sukabumi Public Health Center was mostly high (53.0%). The results of the Chi-Square analysis showed a significant relationship between patient knowledge on adherence (p-value = 0.002 or <0.05) and the relationship between patient attitudes towards compliance (p-value = 0.001).